Mineral Liberation: A Case Study for Buzwagi Gold Mine - Wikedzi, Alphonce; Leißner, Thomas (Tanzania Journal of Science, 2021)
Buzwagi Gold Mine (BGM) process plant was designed such that, after secondary grinding, gold and copper are recovered by flotation. However, the flotation circuit had been inefficient, and as a result, cyanidation of flotation tailings is currently conducted to improve gold recovery. The inefficient flotation is suspected to be due to mineralogical variations of ores treated. Hence, mineral liberation characteristics of three ore blends treated by BGM were investigated by automated Scanning Electron Microscope (SEM) whereby five fractions (i.e. -1 +0.5 mm, -0.5 +0.25 mm, -0.25 +0.125 mm, -0.125 +0.063 mm and -0.063 mm) were used. It was found that pyrite-pyrrhotite is the major valuable phase and the host of gold. Furthermore, pyrite-pyrrhotite was liberated at relatively coarse size (i.e. approx. 200-400 µm). Additionally, quartz, feldspar, muscovite and biotite-chlorite were the main gangue phases. Pyrite-pyrrhotite grain size distribution was coarser than most gangue minerals in the ore blends, indicating that most of the milling energy was lost in grinding of gangue phases. Since gold host phase (pyrite-pyrrhotite) was liberated at coarser sizes, it was concluded that the efficiency of gravity circuit could not be affected. However, the flotation process will still require finer feed (i.e. ≤ 125 µm) for its efficiency. Keywords: Mineral liberation; Gold ore blends; Flotation Performance; Pyrite-pyrrhotite; Automated Mineralogy